CHARACTERIZATION OF DAMAGE IN ALUMINUM NITRIDE SINGLE CRYSTALS BY RBS-C, AN ION BEAM ANALYSIS TECHNIQUE - Hussein, Sarab (An-Najah National University, 2024)
Insulating optical materials such as aluminum nitride (AlN) will play a crucial role in future fusion reactors, particularly in diagnostic systems. AlN is being considered as an insulating coating in some reactor designs due to it is high resistance to chemical corrosion and also exhibits a high thermal conductivity up to 321 W/(m·K). Understanding the degradation mechanisms of AlN under implantation and irradiation is of utmost importance. This study investigated the effect of helium ions on the structure of aluminum nitride (AlN) single crystals using 6 MeV Au+ ions. The crystals were implanted with Au+ ions and analyzed using the Rutherford Backscattering in Channeling (RBS/C) technique across various ion fluences to mimic damage from heavy recoil nuclei. Results showed a gradual increase in damage, measured as a percentage of defects, with increasing ion fluences, reaching saturation at a depth of around 1.3 µm. Monte Carlo McChasy simulations validated the experimental Rutherford Backscattering in Channeling RBS/C data, demonstrating excellent agreement. Transmission electron microscopy (TEM) observations of AlN samples pre-implanted with 6 MeV Au+ ions at room temperature revealed a gradient of defect concentration, with higher densities at the rear of the damaged layer and notably high defect density at the surface. Discrepancies between observed defect sizes and the Stopping and Range of Ions in Matter (SRIM) predictions highlighted SRIM's limitations for high-energy, high-mass projectiles on light targets. X-ray diffraction (XRD) analysis provided insights into strain values influenced by implantation fluence and flux. Despite a slight temperature increase in the highest fluence sample, strain values remained consistent with lower fluences, indicating robust behavior. Elastic strains increased with fluence, reaching saturation at approximately 1.7% and 2.5% for near-surface and peak damage regions, respectively. Challenges in determining near-surface strain due to complex XRD curve shapes were noted, but an overall trend was observed This study offers valuable insights into the structural changes induced by helium in AlN crystals, enhancing our understanding of material responses to irradiation and aiding in the development of predictive models for radiation-induced damage in materials.
وصف الضرر في بلورات نيتريد الألومنيوم المفردة بواسطة RBS-C ، تقنية تحليل شعاع أيون